The effects of aquatic therapy during post-acute neurorehabilitation in patients with severe traumatic brain injury: a preliminary randomized controlled trial. (14th October 2020) - Curcio, A.; Temperoni, G.; Tramontano, Marco; De Angelis, S.; Iosa, M.; Mommo, F.; Cochi, G.; Formisano, R.
ABSTRACT: Objective: The primary aim is to verify the effectiveness of an aquatic training (AT) in inpatients with severe Traumatic Brain Injury (sTBI) on balance. The secondary aims are to explore the effects on gait, activities of daily living, and quality of life, comparing to a land-based conventional protocol. Methods: Two-arm, randomized controlled trial. Twenty inpatients with sTBI, Glasgow Coma Scale score ≤8, and Level of Cognitive Functioning ≥7 were recruited and randomly assigned to the aquatic therapy group (ATG) or to the Conventional Training Group (CTG). Patients underwent 12 individual rehabilitation sessions (3 days/week, 4 weeks), in a rehabilitation pool during the post-acute intensive neurorehabilitation. The primary outcome measure was the Berg Balance Scale (BBS). Secondary outcome measures were the Modified Barthel Index (MBI), Disability Rating Scale (DRS), Tinetti Gait Balance Scale (TBG) and Quality of Life After Brain Injury (QOLIBRI). All the evaluations were performed at the baseline and after 4 weeks of training. Results: The within-subjects analysis showed a significant improvement both in ATG and CTG in MBI, BBS, TBG, and QOLIBRI. Conclusion: Our results may support the use of AT during post-acute phase to improve motor functions and quality of life in patients with sTBI.